IMPROVING STUDENT LEARNING MOTIVATION THROUGH THE USE OF GAMES IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Iman, Khairul; Riyadi, Slamet; Abdi, Hamdani; Susanti, Novi (Amanah Publishing, 2024)
Islamic Religious Education learning is often considered boring and overly theoretical by some students. This often leads to decreased student motivation, impacting the learning process and student learning outcomes. Teachers must employ various strategies and tactics to ensure effective learning. To address this, a game-based learning approach is a creative solution that can make the learning process more engaging and enjoyable. Games serve not only as entertainment but also as an effective learning medium for conveying Islamic values. This study aims to explain the definition, function, benefits, and techniques for using games in Islamic Religious Education learning. The study results indicate that the use of games can increase learning interest, understanding of Islamic concepts, and foster active and collaborative attitudes in the classroom. Games such as digital quizzes, Islamic card games, and role-playing games have been shown to create a more lively and meaningful learning atmosphere. Therefore, it is important for teachers and prospective educators to develop creative learning strategies that are appropriate to the characteristics of today's students.